Survival time of juvenile dogs with oral squamous cell carcinoma treated with surgery alone: A Veterinary Society of Surgical Oncology retrospective study. Issue 4 (27th March 2021) - Sharma, Surabhi; Boston, Sarah E.; Skinner, Owen T.; Perry, James A.; Verstraete, Frank J. M.; Lee, Da Bin; Van Stee, Lucinda L. L.; Thompson, Chris; Boylan, Matthew; McKee, Talon; Bergman, Philip J.
Abstract: Objective: To report the signalment, staging, surgical treatment, and survival time of juvenile dogs treated surgically for oral squamous cell carcinoma (OSCC). Study design: Retrospective study. Animals or sample population: Twenty‐five dogs, <2 years of age with OSCC treated with surgery. Methods: Cases were solicited from the Veterinary Society of Surgical Oncology. Data retrieved included sex, breed, age, weight, clinical signs, tumor location, preoperative diagnostics and staging, histopathological diagnosis with margin evaluation, disease‐free interval, and date and cause of death. A minimum follow‐up time of 3 months was required for inclusion. Results: Eighteen dogs were <12 months of age, and seven were <24 months. Various breeds were represented, with a mean body weight of 22.3 ± 14.4 kg. No dogs had evidence of metastatic disease prior to surgery. All dogs underwent partial maxillectomy or mandibulectomy. Histological margins were complete in 24 dogs and incomplete in one. No dogs had evidence of metastatic disease or tumor recurrence. The median follow‐up time was 1556 days (92 to 4234 days). All dogs were alive at the last follow‐up except for one documented death, due to dilated cardiomyopathy. Median disease‐specific survival time was not reached. Conclusion: The prognosis after wide surgical excision of OSCC in juvenile dogs was excellent. Clinical significance: OSCC in juvenile dogs can be effectively treated with surgery alone.